pointblue/anthropocene: Analysis of Antarctic Anthropocene Impacts - Leo Salas (Zenodo, 2024)
Code (R) and notebooks (jupyter) used in the analysis of data for the paper titled: "Resurgence of the Anthropocene in the Ross Sea, Antarctica", by David Ainley et al. (2024), published in Antarctic Science.